Enhancing Metro’s creative economy: insights from focus group discussions using the business model canvas - Pratama, Yan Aditiya; Wijaya, PG. Wisnu; Putra, Ambar Aditya (PHINISI, 2025)
Nowadays, some of the creative economic potential in Metro, Lampung has not been well-mapped in terms of center, capital, human resources, and marketing, etc. To solve it, the appropriate policies are needed to specify the problems. The purpose of this study is to provide an overview of the human resources potential of the Metro City Creative Industry as initial data for the formation of the Metro Creative Hub and provide references for the form of organization and organization of the Metro Creative Hub. The type of method in this study is qualitative methods using Focus Group Discussions (FGD) and Business Model Canvas. It concluded that respondents wanted an alternative type of creative hub in the form of a coworking space in terms of a creative community network formed from creative actors and the activities they did. From a physical perspective, the creative hub provides a place with spaces to work for creative communities as well as being a business incubator for the creative industry. Physically, the creative hub only covers one place according to its essence as a center.